Penyusutan Aset Tetap Kenderaan Bermotor - Abdullah, Julie; Hasan, Wahyudin; Djarangkala, Azwar (Gorontalo Accounting Journal, 2021)
Fixed assets of motorized vehicles have a relatively short useful life compared assets such as structures and buildings. Besides from that, this object is very prone to loss, damage, and constant depreciation. To minimize the risk in estimating depreciation of fixed assets on a time frame scale, good asset plan is necessary. The goal of this article is to find out which Bone Bolango Regency Financial and Asset Management Agency manages the depreciation of motorized vehicle in the financial statements. The analysis tool use the straight-line method to assess fixed assets, as well as the method used is quantitative descriptive, the aim of obtaining an objective picture of the implementation of depreciation of fixed assets in accordance with Government Regulation Number 71 of 2010 based on financial statement data period 2020. From the results of the research showed that In the activity of determining the value of BPKAD Bone Bolango district not yet in accordance with Government Accounting Standards No. 07 contained in Government Regulation Number 71 of 2010 concerning Government Accounting Standards. In principles of the accounting activity of depreciation of assets, primarily motorized vehicles, the activity of determining the useful life of assets and the depreciation of assets calculation activities of institutional motorized vehicle assets has matched PSAP number 7.